Inalienabilità del bene culturale tra valori estetici e identità collettiva - Cenini, Marta (Cultura giuridica e diritto vivente, 2020)
[Inalienability of cultural property between aesthetic values and collective identity]. The recent phenomenon of deaccessioning puts attention on one of the main issues related to the discipline of cultural heritage and cultural property, in particular its circulation. In the civil law systems, the idea of the inalienability of the cultural goods is currently well established and this implies the inapplicability of the bona-fide purchaser rule to all the goods belonging to the national cultural heritage. However, what is cultural heritage is under discussion and this question also raises delicate questions related to what is collective identity.